Total Internal Reflection End-Pumped Solar Laser with the Solar-to-Laser Conversion Efficiency of 6.09% - Lin Wang; Haiyang Zhang; Dário Garcia; Weichen Xu; Changming Zhao; Anran Guo (Energies)
A novel total internal reflection solar end-pumped laser system has been introduced for the first time, aimed at enhancing the solar-to-laser conversion efficiency. Utilizing a conical solid or cavity reflector, this system refocuses sunlight from a 0.2818 <semantics>m2</semantics> parabolic mirror into a single Ce (0.05 at.%): Nd (1 at.%): YAG crystal rod, measuring 4 mm in diameter and 10 mm in length, thereby promoting total internal reflection and extending the pumping path. Simulation results indicate that under the same solar input power conditions (249.05 W), the conversion efficiencies of the conical solid reflector and cavity reflector systems are 1.2 times and 1.33 times higher than the current highest recorded efficiency of single-rod systems, respectively. At 950 <semantics>W/m2</semantics>, the conical reflector reaches 5.48% efficiency, while the cavity reflector attains 6.09%. Their collection efficiencies are 52.03 <semantics>W/m2</semantics> and 57.90 <semantics>W/m2</semantics>, with slope efficiencies of 6.65% and 7.72%.